Analysis of influence on driver behaviour while using in‐vehicle traffic lights with application of head‐up display. Issue 5 (1st June 2016) - Yang, Bo; Zheng, Rencheng; Yin, Yuandong; Yamabe, Shigeyuki; Nakano, Kimihiko
Abstract : Emerging vehicular communication makes it possible to provide traffic light information to drivers inside vehicles with the application of in‐vehicle devices. However, the effect of this method on driver behaviour is still unclear, and there is concern that the application of in‐vehicle traffic lights may result in driver distraction. This study proposed two modes of in‐vehicle traffic lights to assist drivers: a 'current' mode providing real‐time information of the upcoming ground traffic lights, and a 'predicted' mode offering predicted information regarding ground traffic lights, taking into account the time to arrival at the upcoming intersection. Two kinds of in‐vehicle devices were compared for displaying in‐vehicle traffic lights: a normal 4.3‐inch display and a head‐up display. A driving simulator experiment was executed for 11 subjects, and driver behaviour was evaluated for driving operations and eye‐gaze behaviour. The results demonstrated that disruptive braking and accelerating operations were significantly reduced under the predicted mode, and glance time was significantly shorter for the head‐up display than for the normal 4.3‐inch display. The authors concluded that the predicted mode easily prompts drivers to ecological driving, and that the head‐up display is reliable for providing in‐vehicle traffic light information.